"Ball Don't Lie!" Rasheed Wallace and the Politics of Protest in the National Basketball Association. (June 2016) - Colás, Yago
This analysis offers a contextualized close reading of the phrase "Ball don't lie!" used by former National Basketball Association (NBA) player Rasheed Wallace to protest foul calls. The analysis first explains how "Ball don't lie" counters what can be called "basketball common sense" by analyzing the official language of the NBA concerning fouls, referees, and disputes over foul calls, which it is argued functions as an authoritarian speech act that obscures its own nature. In view of this, it is argued that "Ball don't lie!" counters with a pragmatic intervention in a material and discursive contest between a player and a referee. It is shown how this intervention serves to situate and contextualize the racial politics of basketball in American society. Through this analysis, a sketch of a history of race in the NBA may be seen that focuses on what may be called the "the White basketball unconscious, " and the analysis aims to illuminate how "Ball don't lie" intervenes as a disruptive form of political affirmation, one that, metonymically, resonates beyond the court and into American society more broadly.